2013
DOI: 10.1080/13548506.2013.806814
|View full text |Cite
|
Sign up to set email alerts
|

Psychological distress in asthma and allergy: the Västerbotten Environmental Health Study

Abstract: With the aim to better understand the association between asthma/allergy and psychological distress, it was hypothesized that levels of stress, exhaustion, anxiety, depression, and health worries for environmental pollution would be higher in allergic asthma, allergic rhinitis, and atopic dermatitis than in non-allergic asthma and in referents without asthma or allergy. Taking part in the population-based Västerbotten Environmental Health Study (aged 18-79 years), 76 respondents reported a physician-based diag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 20 publications
1
41
0
1
Order By: Relevance
“…MHW seem to be particularly high among people with self-reported sensitivities [27][28][29], while some evidence supports their role as part of a cognitive-behavioral mechanism that leads to IEI and associated symptoms. Bailer et al [27] found that the association between worries and doctor consultations was explained by IEI-complaints, indicating that increased worries could constitute a risk factor for the development of environmental intolerances.…”
Section: Introductionmentioning
confidence: 99%
“…MHW seem to be particularly high among people with self-reported sensitivities [27][28][29], while some evidence supports their role as part of a cognitive-behavioral mechanism that leads to IEI and associated symptoms. Bailer et al [27] found that the association between worries and doctor consultations was explained by IEI-complaints, indicating that increased worries could constitute a risk factor for the development of environmental intolerances.…”
Section: Introductionmentioning
confidence: 99%
“…Also, in current trends, most researchers believe that there is a bidirectional causal relationship between AR and PD (Chida, Hamer, & Steptoe, 2008;Gelis, Prokopakis, Helidonis, & Velegrakis, 2007;Lind, Nordin, Palmquist, & Nordin, 2014). *Corresponding author.…”
Section: Allergic Rhinitismentioning
confidence: 96%
“…There is an ongoing debate over the relationship of anxiety/depression with AR (Addolorato et al, 1999;Annesi-Maesano et al, 2006;Jernelöv et al, 2009;Lind et al, 2014;Runeson, Wahlstedt, & Norbäck, 2011;Tonelli et al, 2009). According to previous clinical studies, opinions could be classified as: (1) AR associated with both depression and anxiety; (2) Anxiety, but not depression; (3) Depression, but not anxiety; (4) Neither.…”
Section: Allergic Rhinitismentioning
confidence: 98%
“…Таким образом, в самом названии заболевания отображается ведущая роль нервной системы в развитии кожных высыпа-ний. Роль стресса и расстройств нервной системы в развитии АтД не вызывает сомнения и сейчас [13]. Роль вегетативной нервной системы в развитии АтД подчеркивается многими авторами [14].…”
Section: ключевые слова: атопический дерматит дети топическая терапunclassified